2020
DOI: 10.1093/tas/txaa164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus subtilis PB6 and/or chromium propionate supplementation on serum chemistry, complete blood count, and fecal Salmonella spp. count in high-risk cattle during the feedlot receiving and finishing periods1,2

Abstract: The study objective was to determine the effects of Bacillus subtilis PB6 and/or chromium propionate supplementation on serum chemistry, complete blood count, and fecal Salmonella spp. count in high-risk beef cattle during a 56-d feedlot receiving period and the subsequent finishing period. Four truckload blocks of crossbred beef bulls (n=300) and steers (n=84; total n=384; average initial BW = 220 ± 16.2 kg) were sourced from regional auction markets and assigned randomly to treatments arranged in a 2 × 2 fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…On day 140 of the present study, there was numerically greater ( P = 0.34; 0.0 vs. 8.3%) fecal Salmonella prevalence for CLO compared to CON steers. Smock et al (2020b) noted an appreciable decrease in fecal Salmonella prevalence in high-stressed feeder steers supplemented with B. subtilis PB6 on day 28 of the feedlot-receiving period. However, no differences among treatments for fecal Salmonella incidence were noted on day 196 of the feeding period ( Smock et al, 2020b ).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…On day 140 of the present study, there was numerically greater ( P = 0.34; 0.0 vs. 8.3%) fecal Salmonella prevalence for CLO compared to CON steers. Smock et al (2020b) noted an appreciable decrease in fecal Salmonella prevalence in high-stressed feeder steers supplemented with B. subtilis PB6 on day 28 of the feedlot-receiving period. However, no differences among treatments for fecal Salmonella incidence were noted on day 196 of the feeding period ( Smock et al, 2020b ).…”
Section: Resultsmentioning
confidence: 91%
“… Smock et al (2020b) noted an appreciable decrease in fecal Salmonella prevalence in high-stressed feeder steers supplemented with B. subtilis PB6 on day 28 of the feedlot-receiving period. However, no differences among treatments for fecal Salmonella incidence were noted on day 196 of the feeding period ( Smock et al, 2020b ). The lack of detectable Salmonella in these steers could be due to the fact that the steers used in the present experiment were not transitioned through a cattle auction facility.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Alanine transaminase is a marker of liver function, and an increased concentration can indicate liver damage (Pagana and Pagana, 2013 ). In high-risk cattle, Smock et al (2020) also observed a decline in ALT in the first 14 d after feedlot arrival. If liver function is reduced when high-risk cattle arrive at the feedlot, it is not surprising that blood glucose concentrations were also less on day 0 compared with day 14 ( P < 0.01).…”
Section: Resultsmentioning
confidence: 83%
“…During a lipopolysaccharide challenge, supplementing 0.20 mg/kg of dietary DM Cr propionate improved immune response parameters ( Burdick et al, 2011 ). Smock et al (2020a , 2020b ) reported a reduction in first-treat respiratory morbidity (43.9% vs. 35.8%, control or Cr, respectively), and improved immune function by supplementing 0.30 mg/kg dietary DM Cr propionate. In high-stress cattle populations, Cr supplementation with a high-Cr yeast product decreased serum cortisol, increased total immunoglobulin production ( Chang and Mowat, 1992 ), and decreased morbidity ( Moonsie-Shageer and Mowat, 1993 ).…”
Section: Discussionmentioning
confidence: 99%